Climbing the Kilimanjaro: 1861–1889. Local Experiences, European Appropriations and Cultural Hybridisations - (:unkn) unknown (My University, 2023)
Known to Europeans since the middle of the 19th century, Kilimanjaro was quickly perceived as probably the highest peak in the African continent, and soon became the target of Western explorers and mountaineers. Between 1861 (first expedition aiming to reach the summit) and 1889 (when the summit was finally reached), at least ten expeditions set out to conquer the mountain, regularly pushing back the limits of what appears, beyond a certain altitude, as a true pioneering front – for European and African actors alike. This article reviews the conditions of ascent that these different actors met with (whether European expedition leaders or East African guides and porters) on the field, how they reacted to them, and the lessons they learned.
Keywords: African Research